(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2025)
This article aims to analyze the challenges of Angolan Military Justice in the digital age, considering the articulation of the constitutional principles that guide it within the framework of the Constitution of the Republic of Angola (2010). The research adopts a qualitative methodology, with a descriptive and explanatory approach, based on a comparative literature review (with emphasis on Angola, Brazil and other Portuguese-speaking countries) and on documentary analysis of legislation and judicial practices. Initially, the concept of Military Criminal Law is elucidated, which allows the delimitation of the investigated subthemes, including the nature, composition and competences of the Military Court in the Angolan constitutional process and the constitutionalization of military crimes. Finally, the research correlates the foundations of the Rule of Law with the challenges faced by Military Justice in the digital age and artificial intelligence, highlighting the need for military judges to adapt to new technological realities.